Influence of Online Dating Apps on Sexual Risk Behaviors among Homosexual and Bisexual Adolescents and Youths in Thailand: An Online Cross-sectional Survey - Thunyapipat, Chaloempong; In-iw, Supinya; Manaboriboon, Boonying (Siriraj Medical Journal, 2023)
Objective: The internet and social media enhance communication, education, and social connection among users; however, some adverse effects on health are notable, particularly sexual risk engagement and mood problems. Mobile dating applications (apps)/websites facilitate high sexual-risk access, particularly among lesbian, gay, bisexual, transgender, and queer (LGBTQ) individuals. Recognition of the characteristics of using these platforms and identifying factors related to high sexual risk among LGBTQ youths will facilitate both targeting of those at risk and subsequent intervention. Materials and Methods: Adolescents and youths were invited to voluntarily join this study, scan the QR code, and anonymously complete the questionnaires. These validated questionnaires were launched online via a popular platform among LGBTQs during 2017-2018. Multiple logistic regression was employed to identify factors independently associated with high sexual risk among study subjects. Results: Of 360 participants (mean age: 21±2.8 years, range: 11-25), 60.8% self-reported as homosexual, and the rest were bisexual. Median dating app/website usage was 2 (range 1-10). Two-thirds (62.8%) met partners from those e-platforms, and most (79.6%) developed a sexual relationship. Over half (52.2%) did not use a condom, and one-third (30.6%) abused substances during sex. Poor condom compliance, multiple partners, and substance use were strongly associated with individuals who used >2 apps for longer than 3 years. Depression susceptibility was 32.2%, and was related to condom-use failure (p=0.01). Conclusion: Among LGBTQs, the greater the number and longer time exposed to dating apps/websites, the higher the number of sexual risk behaviors. Moreover, unsafe sex increased among individuals at risk for depression.